2023
DOI: 10.3390/ejihpe13020026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prefabricated Construction on the Mental Health of Workers: Systematic Review

Abstract: Despite the significant contribution of the construction industry to national and global economies, the risk it poses to the health and safety of its workers is concerning. With substantial improvement in physical health and safety performance, especially in industrialised and developed economies, attention has shifted to the mental health of construction workers. The construction industry has implemented several worker-focused and management-oriented intervention programs, but problems related to poor mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…Wuni and Shen [56] made significant contributions to the field through qualitative review methods, addressing notable research topics in PCRs. Fagbenro et al [57] performed systematic literature review to identify the influence of PC on mental health of workers. Li et al [58] highlighted the barriers to development of PC in China using the news analysis method.…”
Section: Existing Studies On Pcmentioning
confidence: 99%
“…Wuni and Shen [56] made significant contributions to the field through qualitative review methods, addressing notable research topics in PCRs. Fagbenro et al [57] performed systematic literature review to identify the influence of PC on mental health of workers. Li et al [58] highlighted the barriers to development of PC in China using the news analysis method.…”
Section: Existing Studies On Pcmentioning
confidence: 99%
“…Rasaki Kolawole Fagbenro and others in 2023 identified factors that affect the mental health of construction workers, such as concerns about job stability and work safety, conflicts arising from communication, and challenges to personal well-being from various sources [11]. To address the issue of poor mental health among construction workers, efforts should focus on promoting awareness of mental health literacy and creating awareness of utilizing leisure time for construction workers, with the aim of improving the physical and psychological work environment.…”
Section: Social Considerations In the Construction Periodmentioning
confidence: 99%
“…Comparably, some authors identified 'Stress' as a positive outcome (Fontana,1989; as cited in Chow, 2009) (Item 7 as highlighted in Table 1), and some as negative (Campbell, 2006). Further, as stated by Fagbenro et al (2023), even though there are significant improvements in physical health, notably in safety, in developed countries, some industries still struggle with the problem of poor mental health among their workers. Moreover, according to Bremner et al (2020), stress-related psychiatric disorders exist.…”
Section: Findings and Analysismentioning
confidence: 99%
“…Organisations are concerned mainly with the ability of their employees to execute work competently, effectively, and efficiently (Salam, 2016). Further, Fagbenro et al (2023) identified that the construction industry loses its active workers to mental health challenges and suicide, reducing productivity, contribution to economic growth, and overall workers' living standards in their study related to prefabricated construction and the health of the workers. Several studies on stress management concerning professionals working in different fields, such as education and healthcare, have been conducted (Bradshaw, 1991;Odigie, 2016;Quirke, 2001).…”
Section: Introductionmentioning
confidence: 99%